DIGITALISASI PENCATATAN KADER JUMANTIK MELALUI APLIKASI SMART DBD ZERO DI KELURAHAN PAMULANG TIMUR - Putri Buani, Duwi Cahya; Angraeni Putri, Sukmawati; Setiaji, Setiaji (Jurnal AbdiMas Nusa Mandiri, 2025)
Community service was carried out in partnership with RW 11, Pamulang Timur Sub-district, South Tangerang, as an effort to support the technology-based Dengue Hemorrhagic Fever (DBD) prevention program. The activity was conducted through two stages: training on the use of the SMART DBD Zero application and counseling on DBD prevention. The SMART DBD Zero application is designed to assist Jumantik cadres (larvae monitoring cadres) in recording and reporting mosquito larvae findings more quickly, accurately, and integrally. Meanwhile, counseling was carried out to increase public knowledge regarding the symptoms, transmission, and DBD prevention steps through the 3M Plus principle. The goals of the community service activity were to increase the digital literacy of Jumantik cadres regarding technology, increase the knowledge of Jumantik cadres regarding DBD prevention with 3M Plus, and increase the effectiveness and efficiency of recording mosquito larvae using a website application. The methods used were needs identification, socialization of activities, training on the SMART DBD Zero application, 3M Plus Counseling, and activity evaluation. The results of the activity evaluation used Likert scale questionnaires, pre-tests, and post-tests. The pre-test results showed that the initial level of public knowledge was 55%, which significantly increased to 97% on the post-test following the counseling. Meanwhile, satisfaction with the application training and DBD prevention counseling was above 90%, with a dominant category of strongly agree.